KEPEMIMPINAN BIROKRATIS, GOOD GOVERNANCE, TATA KELOLA MADRASAH, DAN KEPATUHAN ADMINISTRASI - IRMA SEPTIANA; MUHAMMAD; AGUS (UIN Mataram, 2026)
Bureaucratic leadership is still the dominant model in public organizations and educational institutions in Indonesia. In the context of madrasas, this model faces unique challenges because madrasas serve not only as formal institutions, but also as centre’s for the internalization of moral, religious, and social values. This paper discusses the integration of bureaucratic leadership, the principles of good governance, madrasah governance, and administrative compliance, with additional empirical data on madrasas in Lombok. The results of the study show that the application of the principle of good governance can improve administrative compliance, although there are still budget constraints, the quality of human resources, and the old bureaucratic culture. The implementation of digitalization and participatory leadership is a key strategy.